Cochrane Database of Systematic Reviews 2014
DOI: 10.1002/14651858.cd011031.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery for endometriosis

Abstract: There is moderate quality evidence that laparoscopic surgery to treat mild and moderate endometriosis reduces overall pain and increases live birth or ongoing pregnancy rates. There is low quality evidence that laparoscopic excision and ablation were similarly effective in relieving pain, although there was only one relevant study. More research is needed considering severe endometriosis, different types of pain associated with endometriosis (for example dysmenorrhoea (pain with menstruation)) and comparing la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(64 citation statements)
references
References 38 publications
3
52
0
9
Order By: Relevance
“…[5][6][7][8][9] Many clinicians will recommend surgical treatment to improve subfertility in women with mild and moderate endometriosis albeit that this recommendation is based on moderate evidence from two randomized controlled trials (n5382). 10 One further randomized controlled trial 11 not included in the meta-analysis by Duffy et al 10 reported conflicting results.…”
Section: Methods Of Study Selectionmentioning
confidence: 99%
“…[5][6][7][8][9] Many clinicians will recommend surgical treatment to improve subfertility in women with mild and moderate endometriosis albeit that this recommendation is based on moderate evidence from two randomized controlled trials (n5382). 10 One further randomized controlled trial 11 not included in the meta-analysis by Duffy et al 10 reported conflicting results.…”
Section: Methods Of Study Selectionmentioning
confidence: 99%
“…Several different surgical techniques are performed (Table 2), including excision/removal of endometriosis, uterosacral nerve ablation, presacral neurectomy, and hysterectomy with bilateral salpingo-oophorectomy (BSO) (Daniels et al 2010, Healey et al 2014, Posadzka et al 2015), and some techniques provide better symptomatic control than others. For symptom improvement and preventing disease recurrence, endometrioma removal is superior to drainage (Duffy et al 2014, Practice Committee of the American Society for Reproductive 2014). Hysterectomy without BSO is less effective because of continued hormonal stimulation of microscopic endometriotic lesions.…”
Section: Treatmentsmentioning
confidence: 99%
“…Hysterectomy with BSO leads to surgical menopause, which negatively impacts bone and cardiac health. Extreme surgical management is reserved for patients who fail conservative management (Duffy et al 2014, Practice Committee of the American Society for Reproductive 2014). …”
Section: Treatmentsmentioning
confidence: 99%
“…Surgery for endometriosis has been shown to improve pain symptoms when performed at all disease stages 7,8 . Surgical intervention is also recommended for removal of severe disease for infertility, particularly in stage III disease 7,9 .…”
Section: Introductionmentioning
confidence: 99%